Influencia de los proyectos de responsabilidad social en los trabajadores de la empresa savia peru s.a. en el año 2014. - Estrada Olivares, Estrella Olivia (2015)
The present work was performed in order to determine the "Influence of Corporate Social Responsibility actions Internal welfare workers SAVIA PERU SA. -2014 ". This has been considered the type of descriptive research, based on the design description and the sample consists of 71 employees all employed and workers of the company, which applied the methods and techniques of quantitative and qualitative research. The results show that the proyects of internal corporate social responsibility (RSEI) running SAVIA PERU SA contribute significantly to the welfare of workers, because they can improve the following set of factors: physical and mental health, recreation and integration, labor, individuals and families, helping to maintain an adequate quality of life, knowing that the work environment forms a key aspect for the human, thus strengthening their individual-family development and social, and the satisfaction of different needs, also the company SAVIA PERU SA provides an opportunity for workers to effectively influence their own work environment through their participation in social programs that run the company managing to improve self-esteem, growth and job satisfaction.